Manajemen Membangun Dunia Pendidikan Profesional (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
The term management comes from the word "administratie". In a sense, the administration refers to the paperwork in the office. It is in this sense that cause theonset of examples of complaints management that has been alluded to slow, because management is limited in scope as the paperwork. Other uses of "management" comes from english "administration" as "the management of executive affairs". With the limitations of this kind, understanding, then the management at synonym by "management" an understanding of the wider in scope. Management functions in accordance with the performance profile of education in General is carrying out the functions of planning, organizing, staffing, coordinating, leading (facilitating, motivating, innovating), reporting, controlling. In the world of education, directing the term more precise term wear leading to facilitating expansion, motivating, innovating. Furthermore the supervisory function was implemented as part of a managerial execution. On the level of the school, the more supervisors act as "quality assurance"with the task of supervision as an attempt towards a coaching staff to improve and enhance the quality of education that exists now